2016
DOI: 10.3892/mmr.2016.6056
|View full text |Cite
|
Sign up to set email alerts
|

Expression and clinical significance of C14orf166 in esophageal squamous cell carcinoma

Abstract: C14orf166, a 28 kD protein regulating RNA transcription and translation, may serve a critical role in oncogenesis. The aim of the current study was to explore the association between C14orf166 expression and esophageal squamous cell carcinoma (ESCC) and to draw attention to the association between C14orf166 and the initiation, progression and prognosis of ESCC. C14orf166 expression in ESCC and paired normal tissues was detected by immunohistochemical staining, western blotting and reverse transcription-quantit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
(39 reference statements)
1
4
0
Order By: Relevance
“…Moreover, we found that C14orf166 was constantly up-regulated in NSCLC cell lines. These results agree with our previous study of C14orf166 in esophagus squamous cell carcinoma [ 18 ], as well as in other previous studies [ 22 , 26 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Moreover, we found that C14orf166 was constantly up-regulated in NSCLC cell lines. These results agree with our previous study of C14orf166 in esophagus squamous cell carcinoma [ 18 ], as well as in other previous studies [ 22 , 26 ].…”
Section: Discussionsupporting
confidence: 94%
“…In esophagus carcinoma cells, overexpressed C14orf166 has been reported to activate the abnormal JAK2/STAT3 signaling pathway by acting as a JH2-interacting protein, which induces excessive function, initiating carcinogenesis [ 15–17 ]. Additionally, along with our previous research in esophagus squamous cell carcinoma [ 18 ], C14orf166 is found to be overexpressed in several tumor tissues [ 19–22 ]; however, the role of C14orf166 in NSCLC is unknown, and this present study aims to clarify this potency.…”
Section: Introductionmentioning
confidence: 76%
“…Overexpression and activation of this receptor are commonly detected in colorectal cancer [15]. MEK1 can increase cell proliferation through EGF-EGFR-Ras-MEK-MAPK cascade [16]. In concordance with our results of MEK1 expression in ACS, Williet and colleagues [17] have also demonstrated that there is an increasing EGFR expression in the process of colorectal carcinogenesis, from adenomas showing low grade dysplasia (10% overexpression), and high grade dysplasia (77.8%), to carcinoma (100%).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the RTRAF gene overexpression in human nasopharyngeal and cervical carcinoma cells and tissues has been linked to suboptimal patient outcomes, larger tumor sizes, metastasis to lymph nodes, decreased survival rates, and early patient mortality (23,24). Moreover, following the stabilization of RTRAF gene expression, progression and metastasis to lymph nodes were observed in both esophageal and pancreatic cancers (25,26). In both low-grade and high-grade brain neoplasms, the RTRAF gene expression does not exhibit a noteworthy disparity, proposing that the RTRAF gene overexpression is of paramount importance in the genesis of tumors during the initial phases of tumorigenesis (14).…”
Section: Discussionmentioning
confidence: 99%